Recordações mnêmicas do paciente de terapia intensiva: qualidade de vida e prevalência de Transtorno de Estresse Pós-Traumático - Rovatti, Karla Bender (Universidade do Vale do Rio dos Sinos, 2010)
The Intensive Care Unit (ICU) is a site responsible for saving lives, an environment filled with equipment, drugs, high technology and highly qualified technical staff. However, fears, fantasies of death, memories and feelings put the patient in front of a scenario that may leave marks or records mnemonic capable of generating significant psychological effects such as Post Traumatic Stress Disorder (PTSD), affecting the qual ity of life after hospital discharge. Therefore, the purpose of this study was to evaluate the prevalence of PTSD in patients who have ICU stay, raise some risk factors and protective factors for PTSD from record of memories brought by the patient six months after hospital discharge, and correlate PTSD symptoms, quality of life, with mnemonic memories, sociodemographic and clinical variables. Study participants were 41 adult patients who underwent ICU admission in a general hospital in Porto Alegre, mean age 59 years (SD=14,71).The instruments used were: Inventory Katz, Sheet with sociodemographic and clinical variables, Memory Tool, WHOQOL-brief e SPTSS. Descriptive analysis showed the prevalence of PTSD in this population of 24,4%, using a cutoff ≥ 5, women had more PTSD than men (X2=6,99, p<0,05). The t test showed that memories are more meaningful to patients respectively: faces (t=4,88, p<0,05), panic (t=11,17, p<0,001), fear (t=6,99, p<0,05) and pain (t=4,02, p<0,05). The affectionate memories were associated with significantly (t=-2,28, p<0,05) with PTSD and delusional memories correlated significantly to the time of admission (r=0,46, p<0,001). The chi square test showed that delirium clinical variable showed statistical significance relative to PTSD (X2=6,16, p<0,05), the other variables were not significant. The quality of life of patients suffered concussion after admission of the general point of view, presenting – was statistically significant in relation to PTSD in all its dimensions respectively, the hierarchical regression analysis showed that the variables gender and affectionate memories proved to be predictive of PTSD respectively (β=0,44, p<0,01) and (β=0,46, p<0,01). Conclusion: This study identified the prevalence of PTSD in patients six months after discharge and concluded that, despite having identified two predictors of PTSD – gender and affectionate memories – new longitudinal studies are needed in order to know in depth the risk factors and protection in relation to PTSD.
Keywords: Unidade de terapia intensiva; Memórias; Transtorno de estresse pós-traumático; Qualidade de vida; Intensive care unit; Memories; Post traumatic stress disorder; Quality of life; ACCNPQ::Ciências Humanas::Psicologia